Managing Human Resources in the Light of Corporate Culture as a Lever for Supply Chain Performance - Elmortada, A.; Mokhlis, A.; Elfezazi, S.; E.Mokhlis, C. (International Journal of Engineering and Technology, 2019)
In an economic environment increasingly complex and competitive, firms are now aware, more than ever, of the role of the human resources function as being a primary factor to the success and performance of their supply chains. The scope of this article is to highlight the relationship that exists between human resource management and supply chain management. It also explain how human resource management practices affects the supply chain performance while taking into consideration the company culture and under the effect of a human resource management strategies influenced by the increase in terms ofÂ environment competitiveness that results in a variety of business mutationsâ€¦Â Â